KEKERASAN FISIK PADA ANAK DALAM KELUARGA - Affan Yusra; Dinny Rahnayanty; Nurwahidah Marliana; Septiana Amanda Faradila; Zahara Al Munawaroh (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Physical violence against children in the family is a serious problem that affects the child's growth and development and future. Physical violence against children carried out by their parents can include hitting, kicking or using blunt objects. Parents' awareness of the negative impact of violent punishment is still low and this is influenced by many factors such as a lack of understanding about violence, existing traditions of violence, and psychological problems. However, parents often believe that violence is the only solution in raising and educating their children. Several research results show that violence against children in the family is very difficult to reveal in public. Physical violence against children can also be a legacy of intergenerational violence. Violence against children can be defined as incidents of physical, emotional or sexual violence that are often carried out by people who have a close relationship with the child, such as parents or other family members. Violence against children is divided into two types, namely verbal violence and nonverbal violence (psychological and physical violence). The most common form of violence is physical violence. Physical violence against children can result in physical injury, organ damage, and even death. Therefore, efforts are needed to prevent physical violence against children in the family, including increasing parents' awareness of the negative impacts of violent punishment and providing other alternatives in raising children. Apart from that, support from other parties such as the government, NGOs and the general public is also needed to prevent physical violence against children in the family. Efforts to prevent physical violence against children at home are expected to improve children's health and help them develop their potential optimally.